1990
DOI: 10.1001/archderm.1990.01670260037006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of 5% Permethrin Cream and 1% Lindane Lotion for the Treatment of Scabies

Abstract: A multicenter, randomized, investigator-blind controlled trial was conducted to compare the safety and efficacy of a single, whole-body application of 5% permethrin cream with that of 1% lindane lotion for the treatment of scabies in 467 patients. At 14 +/- 3 days after treatment, the mean active lesion count decreased from pretreatment levels of 85 (range, 4 to 600) in both treatment groups to 14 (range, 0 to 133) in the permethrin group and to 15 lesions (range, 0 to 500) in the lindane group. At 28 +/- 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…[18] Oral ivermectin resulted in headache and nausea in four and two patients respectively that subsided spontaneously without any active intervention. Burning/stinging sensation was reported in 9.9%, pruritus in 6.4%, erythema in 2.1%, pain in 1.7%, tingling in 0.9% patients by Schultz et al, [6] as side effects of permethrin, while Chouela et al, [7] reported hypotension, abdominal pain, and vomiting with ivermectin.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[18] Oral ivermectin resulted in headache and nausea in four and two patients respectively that subsided spontaneously without any active intervention. Burning/stinging sensation was reported in 9.9%, pruritus in 6.4%, erythema in 2.1%, pain in 1.7%, tingling in 0.9% patients by Schultz et al, [6] as side effects of permethrin, while Chouela et al, [7] reported hypotension, abdominal pain, and vomiting with ivermectin.…”
Section: Discussionmentioning
confidence: 94%
“…[4] Permethrin 5% cream has been found to be more effective as compared to lindane and is FDA approved for the treatment of scabies. [5,6] In developing countries like India where the disease is largely prevalent in the lower socioeconomic strata, acquiring permethrin is considered an expensive option. Besides, whole body application for hours together is inconvenient and leads to poor compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Norwegian scabies may respond to Lindane plus keratolytics, but multiple applications of Lindane may be required to eradicate the large number of mites seen in Norwegian scabies, and relapses are frequent. Whole-body application of 5% permethrin cream was found to be a safe and effective alternative to 1% lindane lotion for the treatment of ordinary scabies in both adults and children [15, 16]. Recently 2 patients with crusted scabies who failed to respond to topical benzyl benzoate have successfully been treated with a single oral dose of ivermectin [11].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Seven studies assessed the effectiveness of specific drugs: benzyl benzoate, crotamiton, lindane, ivermectin, and permethrin (Table). In 4 of the trials, close and family contacts in intervention and control groups were treated.…”
Section: Interventions For Treating Scabiesmentioning
confidence: 99%